2022
DOI: 10.1038/s41467-022-34189-6
|View full text |Cite
|
Sign up to set email alerts
|

Higher harmonics in planar Hall effect induced by cluster magnetic multipoles

Abstract: Antiferromagnetic (AFM) materials are attracting tremendous attention due to their spintronic applications and associated novel topological phenomena. However, detecting and identifying the spin configurations in AFM materials are quite challenging due to the absence of net magnetization. Herein, we report the practicality of utilizing the planar Hall effect (PHE) to detect and distinguish “cluster magnetic multipoles” in AFM Nd2Ir2O7 (NIO-227) fully strained films. By imposing compressive strain on the spin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
0
0
Order By: Relevance
“…The strained NIO-227 thin films were grown using the "repeated rapid high-T synthesis epitaxy (RRHSE)" method, which utilizes the ablation of two targets (NIO-227 and IrO 2 ) and rapid thermal annealing. 41,42 We observed that controlling the amount of IrO 2 ablation results in a homogeneous and strained NIO-227 film structure and an enhancement of AHE in the NIO-227 film. This enhancement of AHE in NIO-227 films can be attributed to a decrease in defects and structural inhomogeneity.…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…The strained NIO-227 thin films were grown using the "repeated rapid high-T synthesis epitaxy (RRHSE)" method, which utilizes the ablation of two targets (NIO-227 and IrO 2 ) and rapid thermal annealing. 41,42 We observed that controlling the amount of IrO 2 ablation results in a homogeneous and strained NIO-227 film structure and an enhancement of AHE in the NIO-227 film. This enhancement of AHE in NIO-227 films can be attributed to a decrease in defects and structural inhomogeneity.…”
Section: Introductionmentioning
confidence: 83%
“…This distinct behavior of semimetallic NIO-227 films can be elucidated by the compressive strain effect. 41,42 According to previous studies 41,42 of strained NIO-227 films, the valence and conduction bands move and cross near the Fermi level due to compressive strain. Notably, the ρxx reaches its lowest at 90% IrO 2 ablation and slightly increases at 95% IrO 2 ablation.…”
Section: Articlementioning
confidence: 92%
See 2 more Smart Citations